Pelvic Tilt in Patients Undergoing Total Hip Arthroplasty: When Does it Matter? - Maratt, Joseph D. (J Arthroplasty, 2014)
Pelvic tilt (PT) affects the functional anteversion and inclination of acetabular components in total hip arthroplasty (THA). One-hundred and thirty-eight consecutive patients who underwent unilateral primary THA were reviewed. Most cases had some degree of pre-operative PT, with 17% having greater than 10° of PT on standing pre-operative radiographs. There was no significant change in PT following THA. A computer model of a hemispheric acetabular component implanted in a range of anatomic positions in a pelvis with varying PT was created to determine the effects of PT on functional anteversion and inclination. Based on the study results, tilt-adjustment of the acetabular component position based on standing pre-operative imaging will likely improve functional component position in most patients undergoing THA.